The Role of Religius in Moderate the Influence of Organizational Beliefs and Self-Efficiency on Knowledge Sharing Behavior of LPD Employees in Badung District - I Wayan Wirawan; Anak Agung Oka Wisnumurti; A.A. Media Martadiani (International Journal of Environmental, Sustainability and Social Science, 2026)
The role of individual knowledge in the development of an organization, both public and private sector organizations, shows an important role. The need for private sector workers who have knowledge drives awareness of the importance of acquiring knowledge, especially knowledge that is controlled by each individual in the organization. Employee participation in knowledge sharing activities will increase performance and productivity. The process of sharing knowledge in an organization is driven by several factors including organizational trust, self-efficacy and religiosity. This research aims to analyze and explain how religiosity is a moderating variable on the relationship between organizational trust and self-efficacy on knowledge sharing behavior variables. This research was conducted at the Village Credit Institution (LPD) in Badung Regency, Bali Province, which took a sample of 310 respondents using SPSS Version 26. The results of the research show that organizational trust and self-efficacy influence knowledge sharing behavior. This shows that the higher the level of organizational trust and self-efficacy of LPD employees will result in greater knowledge sharing behavior. This research found that religiosity is able to provide a moderating role on the influence of organizational trust and self-efficacy on knowledge sharing behavior, meaning that religiosity strengthens knowledge sharing behavior. . Religiosity is able to play a quasi-moderating role in the influence of organizational trust and self-efficacy on knowledge sharing behavior, meaning that religiosity strengthens organizational trust and self-efficacy to support knowledge sharing behavior.